Entrepreneurial passion and entrepreneurial intention: the mediating role of perceived behavioral control - Ahlem KRAIEM; Houda RAHALI; Ayoub NEFZI (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
Purpose: The objective of this article is to clarify the mechanism through which entrepreneurial passion affects entrepreneurial intention. This article empirically investigate whether perceived behavior control have a mediating effects on the relationship between entrepreneurial passion and entrepreneurial intention. It is based on cognitive perspectives; the present study aimed to identify the impact of entrepreneurial passion on entrepreneurial intention. Design/methodology/approach: The research method is quantitative. The sample of this study comprised 240 respondents from the public of Tunisian project leaders. Data were gathered using a self-report administered questionnaire, and hypotheses were tested with structural equation modelling. Findings:. The results demonstrate that the relationship between passion and intention is mediated by perceived behavioral control. We found that the mediating effect of perceived behavioral control is partial. Implications/recommendations: Our study has some practical implications for the researcher and entrepreneuship education who are directly and indirectly involved in enhancing the growth of entrepreneurship. Practical implications: This article gives rise to a new reflection on the analysis of entrepreneurial behavior based on a psychological and affective approach. Paper type: Research paper